Student Enrollment and Dropout: An Evaluation Study of DCSA Program at Bangladesh Open University - Rashid, Mohammad Mamunur; Jahan, Monira; Islam, Anwarul; Ratna, Meherin Munjarin (International Review of Research in Open and Distributed Learning, 2015)
The aim of this study is to investigate the present status of DCSA program focusing on student enrollment, dropout and completion trends. The study tries to explore the factors that attract or pull students to enroll in the program and push them to dropout from the program. Secondary data analysis and interview are used to generate data. Quantitative analysis for the secondary data is used to explore students’ enrollment, dropout and completion trends. Qualitative approach is used to analyze the information generated from key participants’ interviews. The findings of the study reveal that students’ enrollment and completion trends are not at satisfactory level. The push factors identified from the study are mostly extrinsic or institution related. The factors that need to improve are current instructional strategy, timely delivery of learning materials and provide course related information, strengthen the activities of Regional Resource Centers (RRC) and Sub Regional Resource Centers (SRRC). The findings have some policy implications implying that the policy makers of BOU should take into account to improve the quality of DCSA program offered by BOU through the delivery mode of ODL.